Theoretical analysis of agricultural pricing policy and the problem of financing economic growth - ABDELLAOUI , Yassine (Revue Internationale des Sciences de Gestion, 2024)
The financing of economic growth by means of agricultural pricing policy has long been an issue for both liberal and socialist economists. However, the basic postulates of each school have not been unanimously accepted by the community of economists, since the concepts used are different. But overall, the agricultural pricing policy is considered by some economic theorists to be a solution for saving the national economy from the crisis in which it finds itself. In Morocco, agricultural pricing policy has been characterised by two main features from independence to the present day: a voluntarist strategy characterised by the policy of stabilising the prices of basic food products, and a strategy based on the disengagement of the State from all operations regulating the functioning of the market. The aim of this article is to see how economic thinking has approached the issue of agricultural prices in relation to the question of financing a country's economic growth. The expected outcome of a sound agricultural pricing policy is to improve the living conditions of rural populations, boost citizens' purchasing power and make a significant contribution to development.